Role of R&D Investment on Future Performance: Evidence From Malaysian Companies - Idil Rakhmat Susanto; Noorlailie Soewarno; Bambang Tjahjadi (Institute of Research and Community Outreach - Petra Christian University, 2024)
R&D Investment is an issue that is still interesting in business research today because it constantly explores company development in terms of technology and innovation. Our study intends to investigate the impact of R&D investment on Malaysian company performance in the future. This empirical study uses company financial statement data accessed via the OSIRIS database. The sample is a non-financial company in Malaysia from 2003 to 2019. This study evaluates The hypothesis using unbalanced panel data regression on 460 company years of observation. Our findings indicate that R&D investments have a degrading impact on the performance of Malaysian companies in the future. These findings indicate that companies in developing countries such as Malaysia have yet to give special attention to investing in R&D as the main business strategy.